2012
DOI: 10.1111/aogs.12027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warm ischemia at uterus transplantation in a rat model

Abstract: An extended warm ischemic time has detrimental effects on the survival of the uterus after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…The insufficiency of basic studies in this field was pointed out, and since then, basic research using animal species was started. The animal experiments regarding UTx have been conducted on small animals, such as mice, rats, and rabbits, large animals (including pigs and sheep), and non‐human primates like monkeys and baboons . Many results regarding transplantation techniques, postoperative management, immunosuppression methods, and so on have been obtained …”
Section: Basic Animal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficiency of basic studies in this field was pointed out, and since then, basic research using animal species was started. The animal experiments regarding UTx have been conducted on small animals, such as mice, rats, and rabbits, large animals (including pigs and sheep), and non‐human primates like monkeys and baboons . Many results regarding transplantation techniques, postoperative management, immunosuppression methods, and so on have been obtained …”
Section: Basic Animal Researchmentioning
confidence: 99%
“…The animal experiments regarding UTx have been conducted on small animals, such as mice, [12][13][14][15][16] rats, [17][18][19][20][21][22] and rabbits, [23][24][25][26] large animals (including pigs [27][28][29][30][31] and sheep [32][33][34][35][36][37][38][39][40], and non-human primates like monkeys [41][42][43][44][45][46][47][48] and baboons. [49][50][51][52] Many results regarding transplantation techniques, postoperative management, immunosuppression methods, and so on have been obtained.…”
Section: Basic Animal Researchmentioning
confidence: 99%
“…22 In separate experiments, it was found that the uterus is an organ, i.e., fairly resistant to warm ischemia. 23…”
Section: Ratmentioning
confidence: 99%
“…A total of 25 rats were initially included, but two rats of the UTx-nonTAC animals were found dead on postoperative day 1 (major intra-abdominal bleeding in both cases), and these were excluded from the experiments. Fourteen days after surgery, all the animals underwent a midline laparotomy, and the uteri were evaluated according to a previous validated scale to assess rejection of a murine uterine allograft (28). Uterine samples were collected for histology, immunohistochemistry, and analysis of mRNA expression.…”
Section: Animals and Experimental Designmentioning
confidence: 99%